The Environmentally Conscious Skies: Did the European Union’s Game of Brinksmanship Lead to a Viable Global Plan for Emissions Trading in Aviation? - Darren A. Prum; Kathryn Kisska-Schulze (Washington University Global Studies Law Review, 2015)
Effective January 1, 2012, the European Union (EU) instituted the first emissions trading scheme (ETS) for aviation, which affected the domestic and international commercial airlines flying into and out of the EU. The EU established the ETS to counter the global aviation sector’s role in releasing greenhouse gas (GHG) emissions; however, such measures were met with heavy opposition by foreign countries, the International Civil Aviation Organization (ICAO), various commercial airlines and the Air Transport Association of America (ATA). This Article analyzes the legality of the EU’s unilateral ETS approach with respect to the commercial airline industry, examines the subsequent development of the ICAO’s global market based members (MBM) program, reviews strategic political strategies implemented by foreign nations to counter the EU’s unilateral action, evaluates the ICAO’s recent developments in instituting a global trading scheme to reduce GHG emissions, and analyzes policy issues with respect to the ICAO’s MGM program as it applies to the EU ETS.
Keywords: environment; emissions trade; EU; European Union; aviation; pollution; brinksmanship; airline; industry; ICAO; International Civil Aviation Organization; GHG; emissions